2016
DOI: 10.1038/mto.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling nanotubes: an alternate route for propagation of the bystander effect following oncolytic viral infection

Abstract: Tunneling nanotubes (TNTs) are ultrafine, filamentous actin-based cytoplasmic extensions which form spontaneously to connect cells at short and long-range distances. We have previously described long-range intercellular communication via TNTs connecting mesothelioma cells in vitro and demonstrated TNTs in intact tumors from patients with mesothelioma. Here, we investigate the ability of TNTs to mediate a viral thymidine kinase based bystander effect after oncolytic viral infection and administration of the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 53 publications
(43 reference statements)
1
38
0
Order By: Relevance
“…MSTO-211H (also referred to as MSTO) is representative of the biphasic histologic subtype of mesothelioma, and VAMT is derived from the sarcomatoid histologic subtype. These cell lines readily form TNTs in cell culture, and thus are optimal for characterizing these unique cell protrusions [ 27 , 32 , 33 ]. We have previously noted that TNT formation in MSTO and VAMT cells is upregulated in conditions of metabolic and physiological stress, such as a low-serum, hyperglycemic microenvironment [ 27 ]; actin is uniformly present throughout the length of these TNTs, and ezrin and ZO-1 localize at the bases of TNTs in these cells; MSTO TNTs facilitate intercellular transfer of molecular cargo such as mitochondria and Golgi vesicles [ 27 , 34 ]; and formation of TNTs in these cells can be suppressed via inhibition of mTOR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSTO-211H (also referred to as MSTO) is representative of the biphasic histologic subtype of mesothelioma, and VAMT is derived from the sarcomatoid histologic subtype. These cell lines readily form TNTs in cell culture, and thus are optimal for characterizing these unique cell protrusions [ 27 , 32 , 33 ]. We have previously noted that TNT formation in MSTO and VAMT cells is upregulated in conditions of metabolic and physiological stress, such as a low-serum, hyperglycemic microenvironment [ 27 ]; actin is uniformly present throughout the length of these TNTs, and ezrin and ZO-1 localize at the bases of TNTs in these cells; MSTO TNTs facilitate intercellular transfer of molecular cargo such as mitochondria and Golgi vesicles [ 27 , 34 ]; and formation of TNTs in these cells can be suppressed via inhibition of mTOR.…”
Section: Resultsmentioning
confidence: 99%
“…Our group recently reported the use of this modified transwell method for assessing TNT-mediated bystander effect following oncolytic viral infection [ 33 ]. In that study, the transwell membrane acted as a physical barrier that eliminated gap junction-mediated cell-to-cell spread of a viral thymidine-kinase activated nucleoside analog compound (ganciclovir) that is often used to study the bystander effect.…”
Section: Resultsmentioning
confidence: 99%
“…More efficient spread of the virus, than classical spread by receptor recognition, is direct cell-cell contact Mcdonald et al, 2003). Numerous studies have showed cellular protrusions mediated virus transfer for many viruses, including human T-cell leukemia virus type I (HTLV-1) (Van Prooyen et al, 2010), murine leukemia virus in living cells (Sherer et al, 2007), Marburg virus (Kolesnikova et al, 2007), African swine fever virus (Jouvenet et al, 2006) herpes viruses (Ady et al, 2016;Favoreel et al, 2005;Gill et al, 2008), influenza A viruses (Kumar et al, 2017;Roberts et al, 2015) and human immunodeficiency virus type 1 (HIV-1) (Sowinski et al, 2008). Cell-associated transmission is considered more rapid and efficient because it omits rate-limiting steps of cell-free spread: the release of virus particles, diffusion and entry occurs quickly at cell-cell contacts sites.…”
Section: Introductionmentioning
confidence: 99%
“…Novel method for effective spreading of OVs to tumor sites may be a very attractive option for the therapy of patients with advanced or metastatic disease . Therefore, a well‐defined in vitro model that reflects the spreading of OVs into the vessel, such as occurs in the in vivo microenvironment, can contribute to simulating the assumption of bystander damage and OV spreading …”
Section: Introductionmentioning
confidence: 99%